Pengaruh profitabilitas, likuiditas, leverage, dan ukuran perusahaan terhadap nilai perusahaan - Murti, Anissa Ulfianti; Purwaningsih, Eny (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Currently maximizing the company has become the goal of every company. This can be seen from the value of the stock, if the value of the stock is high then the value of the company will be good. This research aims to determine the effect of profitability, liquidity, leverage, and firm size on firm value. The method used in this research is causal analysis, two or more variables to determine the correlation between the two. The sampling technique used is purposive sampling. The data used in this research is secondary data obtained from the Indonesia Stock Exchange. This research uses 70 sample data from 14 manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2016-2020 period. The data analysis method used is multiple linear regression analysis. The test results show that profitability, liquidity, leverage, and firm size simultaneously affect firm value in the food and beverage sub-sector. Partially, profitability has a significant and positive effect on firm value, liquidity has a significant and positive effect on firm value, leverage has no effect on firm value, and firm size has a significant and positive effect on firm value.